Sistem dan Dunia-Kehidupan Menurut Jurgen Habermas - Hariyanto, Gustaf (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
The presentation in this paper departs from Habermas's description in Technical Progress and the Social Life-World (1971). Technical progress produces a realm or world called the system, the world of engineering, which can be compared with the everyday world, namely the life-world. This description aims to reveal the extreme contradiction between the two which also departs from the thoughts of Snow, Huxley, Schelsky, and Frayer. The approach used in this research is the study of texts: the method of literature or literature review. In this case, a literature search is carried out by reading various books, journals, and other publications related to certain research topics. Checked the list of books and journals related to Habermas, both in private libraries, campus libraries, regional (public) libraries, bookstores, and the internet in the form of e-books and e-journals – browsing websites. From this bibliographic search, several sources were found in the form of books, journals, magazines, and proceedings. In his study, Habermas sees that the two worlds have their interests. That is, the direction of development of both presupposes a reciprocal relationship. However, this relationship can also be unidirectional which can dominate other areas. To avoid this domination, Habermas offers a solution in the form of dialogue, public communication that is free from domination, which can be carried out through political policies. Habermas sees that public communication is the only way to fight the domination of the system. By turning to communication, according to Habermas, pessimism over technical progress that has resulted in disaster for humanity can be overcome.